Diplomasi Olahraga Kosovo sebagai Upaya Membangun Citra di Dunia Internasional Tahun 2014-2021 - Prakoso, Achmad Habib Dwi; Kresnawati, Megahnanda Alidyan (Global and Policy Journal of International Relations, 2022)
ABSTRACTKosovo is a country from Yugoslavia. The Kosovo conflict is a major conflict involving ethnic Albanians and Serbs. In 1999 NATO entered to resolve the conflict with the United Nations. Which makes Kosovo have the opportunity to be independent. In 2008 Kosovo declared its independence in the Kosovo Assembly. And now Kosovo is trying to build an international image and sees sport as an opportunity to bulid an image. Kosovo formed The Olympic Committee of Kosovo (OCK) to participate in Olympic organization IOC (International Olympic Committee). In 2014 IOC issued full acknowledgment of OCK and allowed Kosovo to appear at the 2016 Rio Olympics. According to the IOC, OCK has fulfilled the requirements of the Olympic Charter which contains technically that IOC members are independent countries and internationally recognized. Kosovo also joined FIFA and UEFA in 2016 through voting by member countries. This study uses a literature study method with secondary qualitative data analysis techniques. Through the data that will be elaborated with the theory of sports diplomacy which is then described through the process of image, namely strategy, substance, and symbolic action. Then the result of Kosovo's efforts to build an image in the context of sports diplomacy.Keywords: Kosovo, image, Sports Diplomacy.DOI: https://doi.org/10.33005/jgp.v10i02.3744